Metabolic and immune consequences of antibiotic related microbiome alterations during first-line tuberculosis treatment in Bamako, Mali - Diallo, Dramane; Sun, Shan; Somboro, Anou M.; Baya, Bocar; Koné, Amadou; Diarra, Bassirou; Nantoumé, Mohamed; Koloma, Isaac; Diakite, Mahamadou; Holl, Jane; Maiga, Almoustapha Issiaka; Seydi, Moussa; et al. (Frontiers in Immunology, 2025)
BackgroundIndividuals with a history of tuberculosis (TB) treatment are at a higher risk of experiencing a recurrent episode of the disease. Previous cross-sectional studies identified a connection between dysbiosis (alterations) in the gut microbiota composition and the administration of first-line TB antibiotics. However, these studies have not successfully elucidated this dysbiosis’s resulting metabolic and immune consequences.MethodsIn a longitudinal assessment, we studied the antituberculosis drug-related changes in the gut microbiota’s composition and the resulting functional consequences. Sputum for TB culture, peripheral blood for metabolomics and cytokines analysis, and stool for shotgun metagenomics were collected from TB participants at Month-0, Month-2, Month-6 of treatment, and 9 Months after treatment (Month-15). Healthy controls were sampled at Month-0 and Month-6.FindingsWe found notable differences in gut microbiota between individuals with TB and healthy controls. While gut microbiota tended to resemble healthy controls at the end of TB treatment, significant differences for many taxa persisted up to Month-15. Concurrently, disturbances in plasma metabolites, including tryptophan, tricarboxylic acids, and cytokine levels were observed. Certain fatty acids associated with inflammation pathways negatively correlated with the abundance of several taxa.ConclusionWe observed alterations in the gut microbiota composition and function during treatment and at Month-15. Numerous changes in bacterial taxa abundances and inflammation-linked metabolites did not reverse at Month-15. This study suggests potential influences of anti-TB drugs and the gut microbiome on the disease outcome, response to treatment, and resistance to future TB infections.